Patterns of Verbal and Nonverbal Communication of PAI Teachers in Developing Student Thinking - Yunita Saskia Simbolon; Mardianto Mardianto (Institut Agama Islam An-Nawawi Purworejo, 2023)
This research discusses the Analysis of Verbal and Non-Verbal Communication of PAI Teachers in Fostering the Morals of SDN 09 Tanjung Medan, Labuhanbatu Selatan Regency, this research aims to find out the Verbal and Non-Verbal Communication of PAI Teachers in Fostering the Morals of SDN Students and what factors support and hinder the Communication Patterns of teachers in Fostering the Morals of SDN Students. This research uses descriptive qualitative research, the approach used is a non-verbal communication approach and a communication psychology approach.The research subjects are teachers or educators, and students. Data collection methods with observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation and conclusion drawing. The results showed that Verbal and Non-Verbal Communication of PAI Teachers in Fostering the Morals of Students of SDN 09 Tanjung Medan, Labuhanbatu Selatan Regency, namely the Primary Communication Pattern, using communication symbols, namely verbal and non-verbal symbols and two communication models, namely two-way communication and many-way communication. The supporting factors in the teacher's communication process in fostering student morals are (1) supporting factors of the communication process, namely the application of verbal and nonverbal communication simultaneously. And inhibiting factors (1) obstacles from the communication process, namely two-way communication and many-way communication, (2) authentic or media obstacles, namely obstacles in the form of facilities in schools that still need to be improved.